A novel small-molecule antagonizes PRMT5-mediated KLF4 methylation for targeted therapy - Zhou, Zhuan (EBioMedicine, 2019)
BACKGROUND: Triple negative breast cancers (TNBCs) have a poor prognosis and are not amenable to endocrine- or HER2-targeted therapies. The malignant and invasive feature of TNBCs is correlated with its high cancer stem cell population. Recent results from us and others have unveiled an oncogenic role for the PRMT5-KLF4 axis in regulating tumor progression by orchestrating the stemness in mammary tumor cell as well as genome stability. Methylation of KLF4 by PRMT5 leads to KLF4 stabilization, resulting in promoting mitogenesis. METHODS: We have developed a small molecule inhibitor, WX2–43, that specifically intercepts the interaction between PRMT5 and KLF4, thereby enhancing KLF4 degradation. FINDINGS: Results from our characterization demonstrate that WX2–43 binds to the region between amino acids L400-M500 on PRMT5. Degradation of KLF4 down-regulates KLF4-mediated genes transcription. We have characterized the potent effect for WX2–43 in inhibiting PRMT5-KLF4 binding that, in turns, suppresses tumor progression and induces tumor cell death in both TNBC cultured-cell and animal models. INTERPRETATION: WX2–43-mediated inhibition of KLF4 methylation by PRMT5 could be a potential strategy for anti-TNBC treatment. FUND: This work was supported, in whole or in part, by National Institutes of Health grants CA202963 and CA202948 (Wan), R21HL109654 (Xie), P30DA035778 (Xie and Bahar) and P41GM103712 (Bahar).